Naltrexone Restores Impaired Transient Receptor Potential Melastatin 3 Ion Channel Function in Natural Killer Cells From Myalgic Encephalomyelitis/Chronic Fatigue Syndrome Patients - Cabanas, Helene; Muraki, Katsuhiko; Staines, Donald; Marshall-Gradisnik, Sonya (Frontiers in Immunology, 2019)
Myalgic Encephalomyelitis/ Chronic Fatigue Syndrome (ME/CFS) is a seriously long-term and debilitating illness of unknown cause hallmarked by chronic pain and fatigue, memory and concentration impairment, and inflammation. ME/CFS hypothesis involves ion channel disorders and more specifically impaired Transient receptor potential melastatin 3 (TRPM3) ion channel function, affecting calcium signalling and Natural killer (NK) cell functions. Currently, substances called opioids, agonists of mu (µ)-opioid receptors (µOR), are the strongest painkillers clinically available for people suffering from strong or long-lasting pain characteristic of CFS/ME. µOR have been reported to specifically inhibit TRPM3 and to be expressed in immune cells where they play an immunomodulatory and immunosuppressive role. Naltrexone hydrochloride (NTX) acts as an antagonist to the μOR thus negating the inhibitory function of this opioid receptor on TRPM3. Therefore, understanding the mechanism of action for NTX in regulating and modulating TRPM3 channel function in NK cells will provide important information for the development of effective therapeutic interventions for ME/CFS. Whole-cell patch-clamp technique was used to measure TRPM3 activity in Interleukin-2 (IL-2) stimulated and NTX-treated NK cells for 24 hours on sixteen age- and sex-matched healthy controls and CFS/ME patients, after modulation with pregnenolone sulfate (PregS), NTX and ononetin. We confirmed impaired TRPM3 function in ME/CFS patients through electrophysiological investigations in Interleukin-2 (IL-2) stimulated NK cells after modulation with pregnenolone sulfate and ononetin. Importantly, TRPM3 channel activity was restored in IL-2 stimulated NK cells isolated from ME/CFS patients after incubation for 24 hours with NTX. Moreover, we demonstrated that NTX does not act as an agonist by directly coupling on the TRPM3 ion channel gating. The opioid antagonist NTX has the potential to negate the inhibitory function of opioid receptors on TRPM3 in NK cells from CFS/ME patients, resulting in calcium signals remodelling, which will in turn affect cell functions, supporting the hypothesis that NTX may have potential for use as a treatment for CFS/ME. Our results demonstrate, for the first time, and based on novel patch clamp electrophysiology, potential pharmaco-therapeutic interventions in ME/CFS.